PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN SDI (SURVEY DRAWING INVENTORY) PT.TELKOM AKSES BEKASI - Firqi Ikhsanul Amal; Abdul Gani (Universitas Mercu Buana, 2021)
This study aims to analyze the influence of the Work Environment, Motivation, on Employee Performance. The population in this study were employees of the SDI (Survey Drawing Inventory) of PT. Telkom Access Bekasi. The sample used was 55 respondents. The sampling method uses saturated samples. Data collection methods using survey methods, with the research instrument is a questionnaire. Data analysis method uses Partial Least Square. This research proves that the Work Environment has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance.